Solution q-2r=4

q+r=37

q+r=37

Q-2r=4, therefore: q=4+2r.

Plug the value of q into q+r=37, so you get:

4+2r+r=37

3r=37-4=33

3r=33

Therefore: r=11.

q-2r=4, but r=11, so:

q-2(11)=4

q-22=4

Therefore q=26.

Check if the answer is correct using second equation:

q=4+2r=4+2(11)=4+22=26.

So: q=26 and r=11.

to solve these problems we can solve by substitution or elimination method. Now we use the method of elimination.

The first equation :

q - 2r = 4

second equation :

q + r = 37

now elimination equations 1 and 2

\( q - 2r = 4\\\underline{q+~r= 37}~-\\~~-3r = -33\\~~~~~~~r = \frac{-33}{-3}\\~~~~~~~r = 11 \)**so the value of r is 11**

now find the value of q by inserting r into equation 1

\( q - 2r = 4\\q - 2(11)=4\\q - 22=4\\q=4+22\\q=26 \)**so the value of q is 26**

**So the value of :**

**r = 11**

**q = 26**

RELATED: